Performance vs. reliability adaptive body bias scheme in 28 nm & 14 nm UTBB FDSOI nodes. (September 2016) - Ndiaye, C.; Huard, V.; Federspiel, X.; Cacho, F.; Bravaix, A.
Abstract: This paper shows the advantages of using body bias. Experiments are performed in 14 nm and 28 nm UTBB FDSOI transistors and ring oscillators (ROs). The impact of body bias on performance and reliability is highlighted. The body biasing offers significant advantages for adapting the tradeoff between reliability and performance in logic circuits without changing the design margins. With FDSOI technology, we have an additional degree of freedom of process variability compensation by using body bias voltage (Adaptive Body Bias, ABB) next to supply voltage compensation used before. We show that ABB compensation technique presents better results for a complete power optimization.